2009
DOI: 10.1021/jf9020416
|View full text |Cite
|
Sign up to set email alerts
|

Structural Differences among Alkali-Soluble Arabinoxylans from Maize (Zea mays), Rice (Oryza sativa), and Wheat (Triticum aestivum) Brans Influence Human Fecal Fermentation Profiles

Abstract: Human fecal fermentation profiles of maize, rice, and wheat bran and their dietary fiber fractions released by alkaline-hydrogen peroxide treatment (principally arabinoxylan) were obtained with the aim of identifying and characterizing fractions associated with high production of short chain fatty acids and a linear fermentation profile for possible application as a slowly fermentable dietary fiber. The alkali-soluble fraction from maize bran resulted in the highest short chain fatty acid production among all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
110
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(117 citation statements)
references
References 44 publications
6
110
0
1
Order By: Relevance
“…As already reported by Rose et al (2009), gut microbiota uses a debranching mechanism to metabolise AX making use of bacterial arabinofuranosidases and xylanases (Rose et al 2009). The authors suggested that the highly branched AX promotes the activity of bacterial arabinofuranosidases earlier than the xylanases, in order to remove the arabinose units of the AX side chains enabling the xylanases to reach the xylose backbone (Rose et al 2009).…”
Section: Arabinoxylans Consumptionmentioning
confidence: 88%
See 3 more Smart Citations
“…As already reported by Rose et al (2009), gut microbiota uses a debranching mechanism to metabolise AX making use of bacterial arabinofuranosidases and xylanases (Rose et al 2009). The authors suggested that the highly branched AX promotes the activity of bacterial arabinofuranosidases earlier than the xylanases, in order to remove the arabinose units of the AX side chains enabling the xylanases to reach the xylose backbone (Rose et al 2009).…”
Section: Arabinoxylans Consumptionmentioning
confidence: 88%
“…Studies reported on the AX fermentation by the human intestinal bacteria indicated that fermentation of AX promotes the growth of Bifidobacterium, Lactobacillus and Eubacterium groups (Cloetens et al 2010;Grootaert et al 2007;Gullón et al 2014;Hughes et al 2007;Pastell et al 2009;Vardakou et al 2008) and, in a smaller extent, also promotes the growth of Bacteroides and Clostridium species (Hughes et al 2007). This process results in the formation of bacterial metabolites such as SCFA and specially the increase of propionic acid concentration (Kabel et al 2002;Napolitano et al 2009;Rose et al 2009). Propionate can be absorbed in the gut, entering in the blood stream and reaching the liver via the portal vein, where it has been associated with reduced cholesterol synthesis and improved insulin sensitivity (Grootaert et al 2007;Neyrinck et al 2011;Van den Abbeele et al 2011), but the mechanisms are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that MHN-3 is not digested but is partially absorbed directly into the blood through the intestinal wall to interact with NK cells and macrophages , and then it may modulate the immune responses in not only gut-associated lymphoid tissue but also spleen. Moreover, arabinoxylan from wheat bran inhibits Salmonella colonization in broiler chickens (Eeckhaut et al, 2008), while the different structure was reported among arabinoxy-lan from wheat bran and rice bran (Rose et al, 2010). Hence, it is possible that dietary arabinoxylan rice bran may affect inflammatory responses in chickens.…”
Section: Introductionmentioning
confidence: 99%